Intensive Behavioral Therapy for Obesity Combined with Liraglutide 3.0 mg: A Randomized Controlled Trial. Issue 1 (13th November 2018) - Wadden, Thomas A.; Walsh, Olivia A.; Berkowitz, Robert I.; Chao, Ariana M.; Alamuddin, Naji; Gruber, Kathryn; Leonard, Sharon; Mugler, Kimberly; Bakizada, Zayna; Tronieri, Jena Shaw
Abstract : Objective: The Centers for Medicare and Medicaid Services (CMS) covers intensive behavioral therapy (IBT) for obesity. The efficacy, however, of the specific approach has never been evaluated in a randomized trial, as described here. The 1‐year trial also assessed whether the addition to IBT of liraglutide 3.0 mg would significantly increase weight loss and whether the provision of meal replacements would add further benefit. Methods: A total of 150 adults with obesity were randomly assigned to: IBT (IBT‐alone), providing 21 counseling visits; IBT combined with liraglutide (IBT‐liraglutide); or IBT‐liraglutide combined for 12 weeks with a 1, 000‐ to 1, 200‐kcal/d meal‐replacement diet (Multicomponent). All participants received weekly IBT visits in month 1, every‐other‐week visits in months 2 to 6, and monthly sessions thereafter. Results: Ninety‐one percent of participants completed 1 year, at which time mean (± SEM) losses for IBT‐alone, IBT‐liraglutide, and Muticomponent participants were 6.1 ± 1.3%, 11.5 ± 1.3%, and 11.8 ± 1.3% of baseline weight, respectively. Fully 44.0%, 70.0%, and 74.0% of these participants lost ≥ 5% of weight, respectively. The liraglutide‐treated groups were superior to IBT‐alone on both outcomes. Weight loss in all three groups was associated with clinically meaningful improvements in cardiometabolic risk factors. Conclusions: The findings demonstrate the efficacy of IBT for obesity and the potential benefit of adding pharmacotherapy to this approach.